Correction to: diagnostic accuracy of clinical visualization and light-based tests in precancerous and cancerous lesions of the oral cavity and oropharynx: a systematic review and meta-analysis (2021)
The reference numbers (last column) contained in table 1 are not matching numbers given in the reference list. Table 1 was modified to encompass the correct reference numbers. The original article has been corrected